C-Reactive Protein, Ferritin and D-dimer as Predictors of Covid-19 Severity (Journal of Enam Medical College, 2025)
Background: Coronavirus Disease 2019 (COVID 19) is a novel infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It emerged in Wuhan and has quickly spread across the world. In Bangladesh, the mortality rate in critically ill patients with COVID-19 is high. This study compares biochemical parameters between mild/moderate and severe patients, helping to identify severe or critical patients early. Objective: To identify severe or critical covid-19 patients early by analysis of biochemical parameters. Materials and Methods: This cross-sectional study was done in Intensive Care Unit (ICU) of Enam Medical College Hospital from April 2021 to August 2021. Total 60 Covid positive patients were enrolled. Among them 30 were severe (ICU) patients and 30 were mild/moderate (non–ICU) patients. Results: A comparison of the hematological parameters between the mild and severe groups showed significant differences in lymphocyte, neutrophil, ferritin, D-dimer and CRP levels. Conclusion: The findings suggest that ferritin, D-dimer and CRP levels can be used to detect the severity of COVID-19 patients.J Enam Med Col 2022; 12(3): 127−131